2018
DOI: 10.1016/j.neuroimage.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of non-negative matrix factorization of grey matter in age prediction

Abstract: The relationship between grey matter volume (GMV) patterns and age can be captured by multivariate pattern analysis, allowing prediction of individuals’ age based on structural imaging. Raw data, voxel-wise GMV and non-sparse factorization (with Principal Component Analysis, PCA) show good performance but do not promote relatively localized brain components for post-hoc examinations. Here we evaluated a non-negative matrix factorization (NNMF) approach to provide a reduced, but also interpretable representatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
90
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 74 publications
10
90
2
Order By: Relevance
“…Reconstruction error was relatively stable across all component sets, as was age prediction error for all levels except for n = 20. Overall, age prediction error was in range with previous "brain age" estimates (Ball, Adamson, et al, 2017;Cole et al, 2017;Franke, Luders, May, Wilke, & Gaser, 2012) confirming that utility of NMF for providing useful low-rank representations of large imaging data sets (Varikuti et al, 2018).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Reconstruction error was relatively stable across all component sets, as was age prediction error for all levels except for n = 20. Overall, age prediction error was in range with previous "brain age" estimates (Ball, Adamson, et al, 2017;Cole et al, 2017;Franke, Luders, May, Wilke, & Gaser, 2012) confirming that utility of NMF for providing useful low-rank representations of large imaging data sets (Varikuti et al, 2018).…”
Section: Discussionsupporting
confidence: 66%
“…Overall, age prediction error was in range with previous "brain age" estimates (Ball, Adamson, et al, 2017;Cole et al, 2017;Franke, Luders, May, Wilke, & Gaser, 2012) confirming that utility of NMF for providing useful low-rank representations of large imaging data sets (Varikuti et al, 2018). We performed NMF using five different levels: 2, 5, 10, 15, and 20 and compared how well the resulting components could reconstruct the original data, and how well the resulting timecourses could be used to predict chronological age.…”
Section: Discussionsupporting
confidence: 64%
“…For example, many studies utilized either lifespan (Cole et al, 2017;Liem et al, 2017) or developmental (Sturmfels et al, 2018;Nielsen et al, 2019) cohorts, while the UK Biobank comprised older adults (more than 45 years old). Furthermore, many studies preferred to use structural MRI, instead of RSFC, for predicting age (Cole et al, 2017;Sturmfels et al, 2018;Varikuti et al, 2018). Liem and colleagues (2017) achieved MAEs ranging from 5.25 to 5.99 when using RSFC for predicting age in a lifespan dataset comprising 2354 subjects, which was worse than our MAE.…”
Section: Prediction Performance In the Literaturementioning
confidence: 66%
“…Like before, prediction accuracies for age, fluid intelligence and pairs matching were evaluated based on the Pearson's correlation between predicted and actual measures across subjects within the test set. Since the age prediction literature often used mean absolute error (MAE) as an evaluation metric (Liem et al, 2017;Cole et al, 2018;Varikuti et al, 2018), we included MAE as an evaluation metric. For completeness, we also computed MAE for pairs matching and fluid intelligence.…”
Section: Uk Biobank Training Validation and Testingmentioning
confidence: 99%
“…The Schaefer parcellation is derived using functional MRI data from ~1500 subjects, by integrating local approaches that detect abrupt transitions in functional connectivity patterns and global approaches that cluster similar functional connectivity patterns (Schaefer A et al 2018). Previous research found that the Schaefer parcellation showed convergence with partitions based on structure alone (Varikuti DP et al 2018). A combination of within-area micro circuitry, proxied by brain morphometry, and between-area connectivity enables each area to perform a unique set of computations (Van Essen DC and MF Glasser 2018).…”
Section: Discussionmentioning
confidence: 99%